Lucchesiite, CaFe2+3Al6(Si6O18)(BO3)3(OH)3O, a new mineral species of the tourmaline supergroup. (2nd January 2018) - Bosi, Ferdinando; Skogby, Henrik; Ciriotti, Marco E.; Gadas, Petr; Novák, Milan; Cempírek, Jan; Všianský, Dalibor; Filip, Jan
Abstract: Lucchesiite, CaFe3 2+ Al6 (Si6 O18 )(BO3 )3 (OH)3 O, is a new mineral of the tourmaline supergroup. It occurs in the Ratnapura District, Sri Lanka (6°35'N, 80°35'E), most probably from pegmatites and in Mirošov near Strážek, western Moravia, Czech Republic, (49°27'49.38"N, 16°9'54.34"E) in anatectic pegmatite contaminated by host calc-silicate rock. Crystals are black with a vitreous lustre, conchoidal fracture and grey streak. Lucchesiite has a Mohs hardnessof ∼7 and a calculated density of 3.209 g/cm 3 (Sri Lanka) to 3.243 g/cm 3 (Czech Republic). In plane-polarized light, lucchesiite is pleochroic (O = very dark brown and E = light brown) and uniaxial (–). Lucchesiite is rhombohedral, space group R 3 m, a ≈ 16.00 Å, c ≈ 7.21 Å, V ≈ 1599.9 Å 3, Z = 3. The crystal structure of lucchesiite was refined to R 1 ≈ 1.5% using ∼2000 unique reflections collected with Mo K α X-ray intensity data. Crystal-chemical analysis for the Sri Lanka (holotype) and Czech Republic (cotype) samples resulted in the empirical formulae, respectively: X (Ca0.69 Na0.30 K0.02 )∑1.01 Y (Fe1.44 2+ Mg0.72 Al0.48 Ti0.33 4+ V0.02 3+ Mn0.01 3+ Zn0.01 )∑3.00 Z (Al4.74 Mg1.01 Fe0.25 3+ )∑6.00 [ T (Si5.85 Al0.15 )∑6.00 O18 ](BO3 )3 V (OH)3 W [O0.69 F0.24 (OH)0.07 ]∑1.00 and X (Ca0.49 Na0.45 □0.05 K0.01 )∑1.00 Y (Fe1.14 2+ Fe0.95 3+ Mg0.42 Al0.37 Mn0.03 Ti0.08 4+ Zn0.01 )∑3.00 Z (Al5.11 Fe0.38 3+ Mg0.52 )∑6.00 [ T (Si5.88 Al0.12 )∑6.00 O18 ](BO3 )3 V [(OH)2.66 O0.34 ]∑3.00 W (O0.94 F0.06 )∑1.00 . Lucchesiite is an oxy-species belonging to the calcic group of the tourmaline supergroup. The closest end-member composition of a valid tourmaline species is that of feruvite, to which lucchesiite is ideally related by the heterovalent coupled substitution Z Al 3+ + O1 O 2– ↔ Z Mg 2+ + O1 (OH) 1– . The new mineral was approved by the International Mineralogical Association Commission on New Minerals, Nomenclature and Classification (IMA 2015-043).